Culture upheaval in psychology? ”Late” J.S. Bruner and E.E. Boesch - Pankalla, Andrzej (Studia Psychologica: Theoria et praxis, 2009)
The main aim of the study is to present symbolic action theory (SAT) of Swiss psychologist E.E. Boesch, and “late” (presented comprehensively in “The Culture of Education” in 1996) J. S. Bruners psychoculturalism as two perspectives having one aim - proposing a radical change in approach to understanding psychology: as antireductionistic transdiscipline named cultural psychology with its subject of interest - cultural being.